Fertility decline and economic growth challenges: Japan's struggle amid a demographic crisis - Hamira, Hamira; Atiyatna, Dirta Pratama; Marissa, Feny; Sari, Dwi Darma Puspita; Khairunnas, Khairunnas (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
This study examines the impact of demographic factors, particularly declining fertility rates and an aging population, on Japan’s economic growth from 1960 to 2022. Additionally, it analyzes key macroeconomic variables, including healthcare expenditure, interest rates, and inflation, that influence the country’s economy. Using quantitative time-series data and the Vector Error Correction Model (VECM), this research evaluates the short- and long-term effects of these variables on economic growth. The findings indicate that, in the long run, population aging and high interest rates significantly negatively affect economic growth. In contrast, healthcare expenditure and moderate inflation have a positive impact. Population aging slows economic expansion by increasing pension and healthcare costs, while high interest rates discourage investment and consumption. Conversely, healthcare expenditure, as an investment in human capital, enhances labor productivity, and moderate inflation stimulates economic activity by promoting consumption and investment. However, in the short term, none of these variables exhibit a significant impact on economic growth, suggesting that policy measures and demographic changes require time to influence the broader economy.